Factors associated with nurses' perceptions, their communication skills and the quality of clinical handover in the Hong Kong context - Jack Pun (BMC, 2021)
Abstract Background Clinical handover is a pivotal, high-risk communicative event because it involves the transfer of responsibility and accountability for patients and their care. Nurses' perceptions and their communication skills inevitably impact on their ability of clinical handover. Limited studies have explored nurses' handover practice in the Hong Kong context. This study aimed to identify factors associated with and specific impact paths between the quality, communication skills and nurses' perceptions on clinical handover. Methods A questionnaire survey was conducted immediately after the nurses' training in effective handover communication. A convenience sample of 206 bilingual nursing staff from a local hospital in Hong Kong participated in this paper-and-pencil survey adopted from the Nurses Handover Perceptions Questionnaire survey. Results The path analysis revealed that except the opportunity to ask questions and high perceptions of the ISBAR communication protocol, other factors were significantly correlated with improved quality of handover. In addition, nurses who had updated information were likely to ask more questions and obtain a better understanding of the patient care plan during handover. Conclusions The quality of nursing handover depended on the degree of nurses' grasp of the patient care plan. The ISBAR communication protocol was considered helping nurses to improve their communication skills with other colleagues and indirectly enhance patient's safety. However, although ISBAR facilitated nurses to structure clearer handover communication, it was not the most important predictive factor for determining handover quality.